Patient and public engagement in priority setting: A systematic rapid review of the literature. - Elizabeth Manafò; Lisa Petermann; Virginia Vandall-Walker; Ping Mason-Lai (PLoS ONE)
Background Current research suggests that while patients are becoming more engaged across the health delivery spectrum, this involvement occurs most often at the pre-preparation stage to identify 'high-level' priorities in health ecosystem priority setting, and at the preparation phase for health research. Objective The purpose of this systematic rapid review of the literature is to describe the evidence that does exist in relation to patient and public engagement priority setting in both health ecosystem and health research. Data sources HealthStar (via OVID); CINAHL; Proquest Databases; and Scholar's Portal. Study eligibility criteria i) published in English; ii) published within the timeframe of 2007-Current (10 years) unless the report/article was formative in synthesizing key considerations of patient engagement in health ecosystem and health research priority setting; iii) conducted in Canada, the US, Europe, UK, Australia/New Zealand, or Scandinavian countries. Study appraisal and synthesis i) Is the research valid, sound, and applicable?; ii) what outcomes can we potentially expect if we implement the findings from this research?; iii) will the target population (i.e., health researchers and practitioners) be able to use this research?. A summary of findings from each of the respective processes was synthesized to highlight key information that would support decision-making for researchers when determining the best priority setting process to apply for their specific patient-oriented research. Results Seventy articles from the UK, US, Canada, Netherlands and Australia were selected for review. Results were organized into two tiers of public and patient engagement in prioritization: Tier 1-Deliberative and Tier 2-Consultative. Highly structured patient and public engagement planning activities include the James Lind Alliance Priority Setting Partnerships (UK), Dialogue Method (Netherlands), Global Evidence Mapping (Australia), and the Deep Inclusion Method/CHoosing All Together (US). Limitations The critical study limitations include challenges in comprehensively identifying the patient engagement literature for review, bias in article selection due to the identified scope, missed information due to a more limited use of exhaustive search strategies (e.g., in-depth hand searching), and the heterogeneity of reported study findings. Conclusion The four public and patient engagement priority setting processes identified were successful in setting priorities that are inclusive and objectively based, specific to the priorities of stakeholders engaged in the process. The processes were robust, strategic and aimed to promote equity in patient voices. Key limitations identified a lack of evaluation data on the success and extent in which patients were engaged. Issues pertaining to feasibility of stakeholder engagement, coordination, communication and limited resources were also considered.